(untitled) (Al-Qamar, 2020)
Over the past century, various scholars and writers have worked on the critique and analysis of Qādiānī thought and ideology in the Indian subcontinent. One of these eminent scholars is Pīr Mehr Alī Shāh Golarvī (1859-1937), a well-known spiritual figure of the subcontinent. In his writings and speeches, Golarvī took a hard look at the thoughts and ideas of Mirza Ghulām Ahmad Qādiānī (1855-1908) and his followers. This article studies Pīr Sāhib’s critique on Qādiānism with reference to his book Saif-e- Chishtiā’ī , written in response to Qādiāni’s Aʻjāz al-Masīh and Mawlvī Ahsan Amrohī’s Shams-e-Bāzigha. The study reveals that the writer, by adopting lexical, grammatical, syntactic, logical, allegorical and research style of reasoning, successfully responded the objections of the opponents. He has refuted the arguments of the Qādiānis with their own arguments.